PERANAN EKOSISTEM TERUMBU KARANG DAN UPAYA REHABILITASI DI PULAU METI KECAMATAN TOBELO TIMUR KABUPATEN HALMAHERA UTARA - Rupilu, Krisostomus (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Hein Namotemo, 2022)
The implementation of this service aims to develop an understanding of the role of coral reef ecosystem in the waters, getting to know various coral transplantation methods and skills in transplantation coral reefs for the people of Meti Village. The methods used in the implementation of the service are the stages of counselling and performance in the form of training. Counselling activities carried out through observation stages to find out the condition, problem and work programs of meti village apparatus, furthermore preparation for counselling activities in the form of material concept and training. Participants in counselling activities consist of village official, youth and fisherman of Meti Village. Evaluation results on extension activities show that there is increased knowledge about coral reef ecosystem and their role in the aquatic environment and increased skills in the implementation of coral tansplants.